INNOVATIVE ASPECTS OF DIGITAL TECHNOLOGIES IN TRACTION POWER SUPPLY (Modern American Journal of Engineering, Technology, and Innovation, 2026)
The article studies the process of changing the structure of traction power supply in the context of digitalization, and explores the potential and prospects of introducing information technologies in traction power supply. The article examines and systematizes the factors and conditions that contribute to the large-scale introduction of digital technologies in the field of traction power supply. The article concludes that it is crucial to develop a comprehensive digital transformation in the traction power supply of railways in order to increase the efficiency of the energy system and expand the scope of interaction with external factors that contribute to the overall growth of the national economy.